THE IMPACT OF CİTİZEN JOURNALİSM AND SOCİAL MEDİA İN NEWS COVERAGE OF THE ISRAELİ ATTACKS ON GAZA. - Alakklouk, Bader; Gülnar, Birol (South Asian Journal of Social Sciences and Humanities, 2023)
The advent of social media platforms has brought about significant changes in the relationship between society and communication systems. This transformation has also impacted the way power structures and the masses communicate and interact, leading to the emergence of citizen journalism as a rapidly growing concept. This aticle aims to explore the significance and relevance of citizen journalism during the Israeli attacks on Gaza, which were heavily documented on social media. The article has used qualitative literature review that is flexible and allows the researcher to focus on constructed realities to put together a clear description and analysis of the reality of the influence of citizen journalism on news coverage of Israeli attacks on Gaza. The aticle was limited to journalistic practices on social media and citizen journalism during the Israeli attacks on Gaza.